Efficient management of resources and entities using the HyVonNe P2P architecture. (6th August 2009) - Gianuzzi, V.; D'Agostino, D.; Merlo, A.; Clematis, A.
Grid and P2P environments often require to manage a wide number of distributed and mobile entities. In this paper we present a scalable partitioning technique of the entity space, based on Voronoi diagrams, that is well-suited for distributed applications with dynamically changing topology. In HyVonNe (Hybrid Voronoi Network) architecture, the entity space is partitioned in Voronoi regions, each one including a limited number of entities and managed by a Region Leader. Regions are created and deleted depending on the spatial density of entities and the resulting Overlay Network is used to support routing and searching activities. This two-layered structure (entity space and Voronoi regions) is scalable, extendable, and allows to reduce the propagation of the entity position updates in the network and to maintain the load balancing among regions. The fault tolerance features of HyVonNe are studied as well, simulating two different applications in Grid and P2P environments.